Protective role of antioxidant vitamin E and catechin on idarubicin-induced cardiotoxicity in rats - Kalender,S. (2002)
Idarubicin is an anthracycline antibiotic extensively used in acute leukemia. In the present study we investigated whether vitamin E and catechin can reduce the toxic effects of idarubicin. Vitamin E (200 IU kg-1 week-1), catechin (200 mg kg-1 week-1), idarubicin (5 mg kg-1 week-1), idarubicin + vitamin E (200 IU kg-1 week-1), and idarubicin + catechin (200 mg kg-1 week-1) combinations were given to male Sprague-Dawley rats weighing 210 to 230 g (N = 6/group). Idarubicin-treated animals exhibited a decrease in body and heart weight, a decrease in myocardial contractility, and changes in ECG parameters (P<0.01). Catechin + idarubicin- and vitamin E + idarubicin-treated groups exhibited similar alterations, but changes were attenuated in comparison to those in cardiac muscle of idarubicin-treated rats (P<0.05). Superoxide dismutase and catalase activity was reduced in the idarubicin-treated group (P<0.05). Glutathione peroxidase levels were decreased in the idarubicin-treated group (P<0.05) and reached maximum concentrations in the catechin- and catechin + idarubicin-treated groups compared to control (P<0.01). Malondialdehyde activity was decreased in the catechin + idarubicin-treated groups compared to control and increased in the other groups, reaching maximum concentrations in the vitamin E-treated group (P<0.01). In electron microscopy studies, swelling of the mitochondria and dilatation of the sarcoplasmic reticulum of myocytes were observed in the idarubicin-treated groups. In groups that were given idarubicin + vitamin E and idarubicin + catechin, the only morphological change was a weak dilatation of the sarcoplasmic reticulum. We conclude that catechin and vitamin E significantly reduce idarubicin-induced cardiotoxicity in rats.